A new Chinese species of Indonemoura (Plecoptera: Nemouridae) and a new subspecies of I. nigrihamita Li & Yang - Li, Weihai; Zhang, Qin; Yang, Ding; Yao, Gang (Zootaxa, 2017)
A new species of Nemouridae of the genus Indonemoura Baumann 1975, I. furcoloba Li & Yang, sp. nov., is described from both sexes from Guangxi Zhuang Autonomous Region of southern China. The relationships with related species are discussed. Additionally, a new subspecies is proposed for a population of I. nigrihamita Li & Yang, 2008 from northern Sichuan Province of southwestern China.